2009
DOI: 10.1007/s00030-008-8012-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Partial Regularity Proof for Minimizers of Variational Integrals

Abstract: Abstract. We consider multi-dimensional variational integrals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, note that if f : Ω × R n × R n×n sym → R satisfies a splitting condition f (x, y, z) = f 1 (x, z) + f 2 (x, y) for some strongly symmetric quasiconvex integrand f 1 : Ω × R n×n sym → R of linear growth and f 2 : Ω × R n → R being convex and of at most n n−1 -growth in the second variable, then suitable regularity results can be formulated. Also, SCHMIDT [65] provides an interesting alternative of a partial regularity proof for convex, fully non-autonomous integrands of (super)quadratic growth that does not utilise Gehring's lemma. The drawback here is that does not seem to generalise easily to the quasiconvex situation with (super)linear growth; even if it would, it needed to be compatible with the above proof scheme.…”
Section: Remarks and Extensionsmentioning
confidence: 99%
“…However, note that if f : Ω × R n × R n×n sym → R satisfies a splitting condition f (x, y, z) = f 1 (x, z) + f 2 (x, y) for some strongly symmetric quasiconvex integrand f 1 : Ω × R n×n sym → R of linear growth and f 2 : Ω × R n → R being convex and of at most n n−1 -growth in the second variable, then suitable regularity results can be formulated. Also, SCHMIDT [65] provides an interesting alternative of a partial regularity proof for convex, fully non-autonomous integrands of (super)quadratic growth that does not utilise Gehring's lemma. The drawback here is that does not seem to generalise easily to the quasiconvex situation with (super)linear growth; even if it would, it needed to be compatible with the above proof scheme.…”
Section: Remarks and Extensionsmentioning
confidence: 99%
“…We further deduce an immediate consequence of the previous two theorems: we first recall that in the previous two theorem we have only considered integrands f under the mixed continuity respectively Hölder continuity condition (1.3), namely on f with respect to x and on D z f with respect to (x, u). The corresponding result under the continuity respectively Hölder continuity condition (1.4) on f with respect to (x, u) now follows by an observation of Giaquinta and Giusti [32, p. 247], see also [59,Appendix A]: it was shown that if ω(·) denotes the modulus of continuity of f , then the growth condition on D zz f in (1.9) 2 allows to conclude that D z f has the corresponding (and optimal) modulus of continuity ω(·) (and no further assumption on ω is needed). Hence, we also have: In case of Theorem 1.1 it is however not clear whether the result under the assumption (1.4) follows from the one under the the assumption (1.3), since in the statement it was not required that second order derivatives of f are bounded uniformly (with a suitable growth condition in the gradient variable).…”
Section: Beckmentioning
confidence: 61%
“…and c depends only on n, N, p, ν, L, γ and M (cf. [59,Lemma 4.3] for the convex situation in the superquadratic case). The same inequality holds true for quasi-convex functions f not depending explicitly on u, provided that the radius is sufficiently small in dependency of p, ν, L and ω 1 (·).…”
Section: Remark 32mentioning
confidence: 99%
See 2 more Smart Citations